The Grand Tradition and People's Tradition of Malay Textile Culture Are Geared Towards Meeting the Local Demand for Textiles in the Malaysian Textile Market - Muhamad Amin, MOHD JAMIL BIN MUHAMAD AMIN; Arba’iyah Ab. Aziz,; Nor Azlin Hamidon,; Qistina Arsyad, (Research in Management of Technology and Business, 2024)
The history of Malaysian textiles gives much colour to Malaysian local textile demand, which started from the early era till the modern day of Malaysia. Malay traditional textiles are considered fundamental elements of Malaysian textile culture. The main issues of local demand and changing of textile culture happened into Malaysian local market, and it was worsted by imported fabric from India and Pakistan into Malaysian market. This paper aims to discuss Malay grand tradition and people’s tradition culture influencing the local Malaysian textile market. The researcher deeply studied the theory of this textile tradition to evaluate the research findings and conclusion.